LAW ENFORCEMENT AND LEGAL AWARENESS OF FEMALE PRISONERS IN CORRECTIONAL INSTITUTION OF PONOROGO - Dewi Iriani (Legal Standing : Jurnal Ilmu Hukum, 2018)
Female prisoners actually have 15 trials to attend or 4 months in duration. However, most of them do not have adequate understanding concerning this legal process. Thus, this study is conducted as a field research by using qualitative approach. This study tends to describe the law enforcement and the legal awareness of female prisoners in correctional institution in Ponorogo. Moreover, how the coaching process given by the prison officers is conducted is another matter to be discussed. The result of this study presented that mostly, female prisoners are sentenced for 3-9 months in prison, but it turns out to be 1-3 months due to imprisonment. Had the verdict is responsibly announced and conducted, it will be appropriate. However, the fact is that the law enforcer, i.e. judge, police officer, prosecutor, and prison officer ask for some money from the female prisoners. This action, of course is breaking the law. After being sentenced, female prisoners actually realized that they are guilty. In this case, the coaching process in correctional institution in Ponorogo has conducted in a good way. However, the coaching process is not gradually conducted when the prisoners are released.